Development of Tourism Learning Media of Smkn 2 Batam Using The MDLC Method - Aldi Rinalta; Zulkarnain Zulkarnain (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
In particular, industrial developments that contradict labor qualifications in administration and tourism have increased the demand for labor in these fields. Realizing this, in 2005, the Batam City Government took proactive measures to develop human resources in Batam City by holding a Vocational High School program located in Batam Center; Batam 2 State Vocational School was still using the online learning system due to the rampant virus disturbance, namely COVID 19. Data is a series of reports, figures, objects, symbols, & descriptions collected from various sources. Data collection makes an excellent decision to serve as an information bridge for launching new products if it is in the marketing realm. In practice, there is also a preference for collecting data using an online communication message called WhatsApp and using the exclusive interview method to become a mediator between the author and Ms. Herlina. This implementation has increased the interest of Batam 2 SMK Negeri 2 students in packaging tourism learning media products regarding transfer in, transfer out, and the transfer process. The results of this study are in the form of making learning media at SMK Negeri 2 Batam in the vocational tourism sector; several animations need to be repaired again using the MDLC stages contained in the testing section.